Nursing competencies in the care of patients with stroke who are eligible for thrombolytic therapy - Marcon Fochesatto, Michele (2025)
Introduction: Ischemic stroke is treated with thrombolytic therapy, applied even in the acute phase, promoting a significant improvement in the after-effects caused by this condition. Considering the complexity of thrombolytic therapy, it is necessary for nurses to understand the skills required to assist in care. Objective: To identify scientific evidence about the competencies of nurses in the care of patients with stroke who are eligible for thrombolytic therapy. Methodology: An integrative review consisting of six stages (elaboration of the question, literature review, data collection, analysis, discussion, and presentation),  conducted in MEDLINE, LILACS, BDENF, IBECS, PubMed, Scopus, Web of Science, Embase, and CINAHL databases. The search was carried out between August and September 2022 using primary studies as the inclusion criteria: free of charge, fully available electronically, published in English, Portuguese, or Spanish. Initially, 2.830 studies were obtained, which underwent a selection process that included only those studies that met the previously established criteria. Results: Based on the twelve studies included in this review, competencies focused on three care activities were identified: care management such as teamwork; codes; flows and protocols; patient care before, during, and after the use of thrombolytic therapy; and education health education for staff, patients, and families. Conclusion: The findings of this review highlighted the nurses' competencies in the care of patients eligible for thrombolytic therapy, which encompass different areas of the nurse's work. For this study, assistance competencies prevailed, followed by management competencies.